Implementasi Personal Selling dan Word Of Mouth dalam Mempertahankan Loyalitas Pelanggan PT Putra Abadi Jaya Mandiri - Anatha Tri Anzani; Rindana Intan Emeilia (Institut Nalanda, 2024)
In an era of increasingly intense business competition, maintaining customer loyalty is key to a company's success. Loyal customers not only provide ongoing revenue contributions but also act as promoters through positive recommendations. Many modern construction companies utilize social media for sales. However, PT Putra Abadi Jaya Mandiri still relies on traditional methods through Personal Selling and Word of Mouth marketing strategies. This study aims to understand the implementation of Personal Selling and Word of Mouth in maintaining customer loyalty at PT Putra Abadi Jaya Mandiri. The method used is descriptive qualitative research, with data collected through interviews, observations, and documentation. The results show that PT Putra Abadi Jaya Mandiri implements Personal Selling in three forms: Field Selling, Retail Selling, and Executive Selling. Personal Selling is conducted through stages of prospect selection, pre-approach, approach, presentation and demonstration, handling objections, closing, and follow-up with customers. The implementation of Word of Mouth is carried out by applying the 5T model: Talkers, Topics, Tools, Talking Part, and Tracking.